Biblioterapia no âmbito hospitalar: projeto turma da leitura - VIEIRA, Nilcidelia dos Santos (2019)
It emphasizes the importance of the biblioterapeutic activities in the humanization of the hospital environment and its contribution to the oncological treatment of hospitalized children. The general objective is to investigate from the perceptions of the volunteers of the Turma project of the reading of the Children's Hospital of Belém on how the bibliotherapy can aid in the recovery of these children. It has as specific objectives to identify in the literature how the bibliotherapy can contribute in the treatment of hospitalized children, to verify in loco the biblioterapeutic techniques applied by the volunteers in the project and to question the volunteers of the Turma da Reading project based on their perceptions about how therapy through books can help in the treatment of children with cancer. It presents as qualitative exploratory research for the collection of bibliographic material in websites, articles, books and database and conducting field research in the data collection through an observation card and questionnaires addressed to the volunteers of the Reading Group project. As a result, it is evident from the perspective of the volunteers that the bibliotherapy contributes to ease the stress, pain, suffering and anguish caused by the hospitalization process and through the data collected and exposed through graphs, it is concluded that the project has obtained results the short time of development.